The influence of multi-stenosis in the left coronary artery subjected to the variable blood flow rate. Issue 1 (1st July 2021) - Kamangar, Sarfaraz; Ameer Ahamad, N.; Nik-Ghazali, N.; Anqi, Ali E.; Algahtani, Ali; Ahamed Saleel, C.; Javed, Syed; Tirth, Vineet; Yunus Khan, T.M.
Abstract : Purpose: Coronary artery disease (CAD) is reported as one of the most common sources of death all over the world. The presence of stenosis (plaque) in the coronary arteries results in the restriction of blood supply, leading to myocardial infarction. The current study investigates the influence of multi stenosis on hemodynamic properties in a patient-specific left coronary artery. Design/methodology/approach: A three-dimensional model of the patient-specific left coronary artery was reconstructed based on computed tomography (CT) scan images using MIMICS-20 software. The diseased model of the left coronary artery was investigated, having the narrowing of 90% and 70% of area stenosis (AS) at the left anterior descending (LAD) and left circumflex (LCX), respectively. Findings: The results indicate that the upstream region of stenosis experiences very high pressure for 90% AS during the systolic period of the cardiac cycle. The pressure drops maximum as the flow travels into the stenotic zone, and the high flow velocities were observed across the 90% AS. The higher wall shear stresses occur at the stenosis region, and it increases with the increase in the flow rate. It is found that the maximum wall shear stress across 90% AS is at the highest risk for rupture. A recirculation region immediately after the stenosis results in the further development of stenosis. Originality/value: The current study provides evidence that there is a strong effect of multi-stenosis on the blood flow in the left coronary artery.